RUSSIAN, PROPORSIONAL PUBLIC ASSOCIATIONS, SOW-POLITICAL MOVEMENTS OF SEVASTOPOL AND CRIMEA (1991 - 1997) - Inna Ostrovskaya (Гуманитарные и юридические исследования, 2021)
The article reveals the process of emergence and formation of public associations initiated by Russian, Russian-speaking citizens of the Crimean region in the conditions of state construction in the Ukraine in the first half of the 1990s. The actual aspects of the representation of Russian ethnic interests in the period indicated are revealed. The activity of the leading political forces of the peninsula of that period is revealed: the Crimean Republic movement, the Russian community of Crimea, the Russian community of Sevastopol and other public associations. The main directions of activity of public associations and socio-political Russian and Russian-speaking movements of Crimea and Sevastopol in 1991-1997 are speciied. The process of creation and transformation of pro-Russian public associations in Crimea and Sevastopol after the collapse of the USSR is analyzed. For the first time, the specifics of the activities of public organizations and movements in the Crimea and Sevastopol have been determined. The activities of Russian charitable foundations are being considered to support the Russian cultural space on the peninsula. Particular attention is paid to the role of the Black Sea Fleet in facilitating the work of various Russian charitable foundations, non-governmental organizations. A historical retrospective of the activities of organizations and socio-political movements allows us to conclude that the Russian and Russian-speaking community are active in the Crimea in defending their rights and freedoms in the irst years of state formation in the Ukraine. The material presented helps to understand the peculiarities of the political processes unfolding in the Crimea in the first half of the 1990s.